Systematic study of proton-induced spallation reactions with the Constrained Molecular Dynamics (CoMD) model - Assimakopoulou, A.; Souliotis, G. A.; Bonasera, A.; Veselsky, M. (HNPS Advances in Nuclear Physics, 2019)
Proton – induced spallation reactions on 238U, 208Pb, 181Ta and 197Au targets at high energies were studied and investigated using the microscopic Contrained Molecular Dynamics (CoMD) model. Total fission cross sections, the ratio fission cross section to residue cross section, mean kinetic energy of fission fragments, mass yield curves and the number of nucleons emitted, before and after scission, as well as the total nucleon multiplicity were calculated using the CoMD model and compared with experimental data from the literature. Some of our calculations showed satisfactory agreement with available experimental data.The calculations of cross sections and the ratio fission cross section to residue cross section as a function of the proton energy gave us the opportunity to estimate observables for unmeasured nuclides.